Meckel's diverticulum: new solutions for an old problem?. Issue 2 (21st October 2015) - Chauhan, Abhishek; Suggett, Nigel; Guest, Peter; Goh, Jason
Abstract : Meckel's diverticulum (MD) is the most commonly encountered true diverticulum in the small bowel. Although overall a rare cause of gastrointestinal bleeding, it remains an important differential in a child/young adult presenting with lower gastrointestinal bleeding. We present two MD cases, one associated with brisk bleeding resulting in haemodynamic instability and the other in insidious blood loss causing symptoms of chronic iron deficiency. These cases illustrate the heterogeneous nature of the clinical picture associated with Meckel's diverticulae, a condition most gastroenterological and surgical units will encounter. We subsequently discuss the diagnostic and management dilemma Meckel's diverticulae pose and appraise the latest evidence and management strategies in this regard.